2019
DOI: 10.1088/1361-6528/ab0830
|View full text |Cite
|
Sign up to set email alerts
|

Percolation-amplified infrared sensitivity in titanium oxide-multi-walled carbon nanotube composite films

Abstract: Titanium dioxide (TiO2)-multi-walled carbon nanotube (MWCNT) thin films were prepared and studied systematically for the effects of the concentration of MWCNTs on the electro-optical properties. Result shows that the addition of MWCNTs not only improves the optical absorption and electrical conductivity, but also reduces the 1/f noise of the films. Percolation phenomenon is observed at MWCNT concentrations of 0.20–0.25 wt%. In this concentration range, the composite films exhibit an abrupt rise of the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…4a). This suggests an electrical percolation phenomenon in the DAST-CNT composite films, as previously observed in the TiO 2 -CNT and Na 3 MnCO 3 PO 4 -carbon black composites (Liang et al 2019;Wang et al 2015b). Similarly, R RT of the DAST-G composite films also drastically decrease with the increase of the G concentration, and an electrical percolation phenomenon is seen at 2.0 wt% G in the DAST-G composite films.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…4a). This suggests an electrical percolation phenomenon in the DAST-CNT composite films, as previously observed in the TiO 2 -CNT and Na 3 MnCO 3 PO 4 -carbon black composites (Liang et al 2019;Wang et al 2015b). Similarly, R RT of the DAST-G composite films also drastically decrease with the increase of the G concentration, and an electrical percolation phenomenon is seen at 2.0 wt% G in the DAST-G composite films.…”
Section: Resultssupporting
confidence: 78%
“…2b). In this case, continuous conductive networks are formed, with which electrons can hop across and/or tunnel through the interfaces between the adjacent CNTs (Liang et al 2019). But if more CNTs are added to DAST, only a slight decrease of R RT with the CNT content is seen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a metal oxide semiconductor, titanium dioxide (TiO 2 ) has attracted much attention because of its nontoxic, high chemical stability, high dielectric coefficient, diverse and straightforward preparation methods [16]. TiO 2 is widely used in sensitized solar cells, gas sensors, resistance switch storage, photocatalysis and memristor [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is widely used in sensitized solar cells, gas sensors, resistance switch storage, photocatalysis and memristor [17][18][19][20][21]. TiO 2 can be widely used in these fields related to its structure and properties [16]. Non-stoichiometric titanium oxide (TiO 2−x ) means that Ti has different chemical states Ti 3+ and Ti 4+ , corresponding to Ti 2 O 3 and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Following this work, in 2019, Liang et al synthesized another metal-oxide/MWCNT hybrid (Ti dioxide, TiO 2 /MWCNT) and studied its thermal characteristics to obtain a RT-TCR value of ∼2.93%/K (Figure d). In this study, the composite was formed by spraying MWCNTs on top of a sol–gel-synthesized TiO 2 film . At the end of 2019, Nandi et al demonstrated ∼486% enhancement of the RT-TCR of MWCNT by coupling it with VO x .…”
mentioning
confidence: 99%